Seasonal changes in the fatty acid profile of Cystoseira crinita Duby, 1830, distributed on the Sinop Peninsula Coast of the Black Sea - Melek Ersoy Karaçuha; Gökhan Yıldız; Ali Karaçuha (Journal of Advanced Research in Natural and Applied Sciences)
This study aimed to determine the fatty acids profile and seasonal change in Cystoseira crinita Duby, 1830 from the Sinop Peninsula coasts. The fatty acids profile was analyzed by GC/MS and their seasonal variation was studied. Along the sampling, it was possible to identify 37 different fatty acids in C. crinita, from C4 to C22. It was determined that palmitic acid was the most abundant fatty acid in all seasons, and further, the season which provided the highest contents of SFA, PUFA, and MUFA was winter. As a matter of fact, in our study, it was determined that the highest PUFA values ranged from 40.63% in winter to 32.23% in summer. It has been determined that the MUFA value varies between 25.88% in winter and 30.79% in summer, and the SFA value varies between 33.50% in winter and 35.98% in summer. In this study, the PUFA/SFA ratio of C. crinita was determined to change between 1.01% - 1.21% from winter to summer. In addition, the total -6/-3 PUFA ratio was found to be greater than 1 and ranged from 1.61 (winter) to 2.07 (summer). The atherogenicity and thrombogenicity index and h/H ratio were calculated from the fatty acid profiles of C. crinata, and the AI index was determined to change from 0.71 (winter) to 0.74 (autumn), TI index was 0.44 winter) to 0.58 (in summer). The h/H ratio of 1.71 (summer) to 2.00 (winter) was calculated. These results of our study showed that the seasons have a significant effect on the fatty acid profile and the fatty acids in C. crinita may have important contributions to human nutrition. For this reasons, it is thought that it is extremely important to reveal the nutritional content of different seaweed species that spread in the seas of Turkey and to observe the seasonal changes in their contents.